Do Growth-Limiting Temperatures at the High-Elevation Treeline Require an Adaptation of Phloem Formation and Anatomy? - Schröter, Dennis Marko; Oberhuber, Walter (Frontiers in Forests and Global Change, 2021)
Low temperatures during the growing season restrict the growth of trees at high elevations and lead to the formation of the high-elevation treeline. To ensure the survival and growth of trees in such extreme locations, sufficient vascular transport capacity - enabled by vascular anatomical characteristics - is required. However, in contrast to the xylem, only little is known about the effects of low temperatures on the anatomy and formation of the phloem as important nutrient- and signal-conducting tissue. In this review, known findings of cold-induced changes in the anatomical and phenological properties of vascular tissues are used as starting points to discuss how low temperatures might affect phloem formation at the treeline and how this conductive tissue might adaptively respond to this growth-limiting environmental variable. Data currently available suggest that low temperatures lead to changes in the anatomy and phenological development of the phloem. In order to ensure the functionality of the phloem and thus the survival of trees at the high-elevation treeline, appropriate adaptations to the prevailing low temperatures are therefore to be expected and are discussed in this review.